Teleportation of a Product State of an Arbitrary Single-Particle State (Journal of Atomic and Molecular Sciences, 2012)
This paper proposes two schemes for teleporting a product state of an arbitrary single-particle state from a sender to a receiver via a four-particle entangled cluster state. The two different quantum channels are used, while the successful probabilities of these two schemes are different. In the first proposal, the successful probability is 1.0 and in the second proposal, the successful probability is $4q^2$ if the receiver performs an appropriate unitary operation.